Early complications of ultrasound guided central vein catheterization in children - Arda, Mehmet Surhan (International Surgery Journal, 2018)
Background: Since mid-20th century Central Venous Catheter (CVC) has been in use. Cut-down was the initial approach that was followed by Seldinger method. Thereafter, anatomic land-mark has been recommended and finally it was switched to ultrasound (USG) guidance. In adults the lower complication and higher success rates of USG guided catheterization has been reported. However, in children, although it was accepted that USG guidance lowers puncture rates, increased success and decreased complication by USG was controversial. Methods: Between 01/07/2014 and 31/12/2017 records of patients that were younger than five years old and that were undergone USG guided CVC placing have been extracted. The early complications due to catheterization was evaluated. Results: A total 259 patients met our criteria. All of them have placed catheter successfully whereas mean puncture rate was 1.32. The 18.9% of them necessitated repetitive procedures of whom 44.9% (n= 22) of them have been catheterized from the previous central line. Thrombosis was detected in only 2.7% (n= 7) of them. Arterial puncture was noticed in four. Conclusions: USG guided central vein catheterization is safe and reliable with lower complication. It could be speculated that lower puncture rates might have great influence on patency of vessels.